Pengaruh Perceived Organizational Support (POS) terhadap Organizational Citizenship Behavior (OCB) melalui Employee Development (ED) dan Organizational Commitment (OC) sebagai Variabel Mediasi pada Tenaga Kependidikan di Salah Satu Perguruan Tinggi Swasta - Vinna Yovita Narwastu; Deborah C. Widjaja; Roy Setiawan (Jurnal Manajemen dan Organisasi, 2023)
Education staff need to have OCB, namely working in accordance with job responsibilites and even exceeding them to increase organizational effectiveness. ED and OC have an important role in creating OCB and are a form of POS (organizational support). Therefore, the role of mediation in ED and OC is important to study. Quantitative research methods using a sample of 140 respondents using nonprobability sampling and purposive sampling techniques, with the criteria for permanent employee status and having worked at least 2 years at one of the private higher education in Surabaya. Test the validity and reliability using SPSS version 25, while data analysis using SmartPLS. The results show that there is a significant effect on POS to ED, ED to OC, OC to OCB, and POS to OCB through ED and OC as joint mediation. On the other hand, there is no significant effect on the relationship between POS to OC, POS and ED to OCB, as well as POS to OCB via ED or OC as independent mediation. The research results for the leaders of private higher education were examined so that leaders can show organizational support in the form of respect for the contributions that have been made by education staff so that work abilities can be improved through employee development efforts and organizational commitment will be higher. In addtion, education staff will want to help provide suggestions or input to their co-workers, so that work will be more effective without having to be given orders.